Epilepsy in pregnancy - Tomson, Torbjörn (BMJ Publishing Group Ltd., 2007)
This article explores the therapeutic problems that arise when a patient with epilepsy on treatment becomes pregnant and needs both effective seizure control and attention to the safety of her fetus